A STUDY OF THE RELIABILITY AND VALIDITY OF THE TURKISH VERSION OF THE WALTER REED VISUAL ASSESSMENT SCALE IN ADOLESCENTS WITH IDIOPATHIC SCOLIOSIS - KURU ÇOLAK, TUĞBA (My University, 2020)
Objective: The Walter Reed Visual Assessment Scale (WRVAS) was developed to evaluate deformity perception in patients with idiopathic scoliosis. The WRVAS has been shown to have a strong internal reliability and a high validity. This study aimed to determine the reliability and validity of the Turkish version of the WRVAS (WRVAS-TR). Materials and Methods: The translated Turkish version of the WRVAS was administered twice to 58 patients in a one-week interval to test the reliability of the scale. Cronbach’s alpha coefficient was used to assess the internal consistency. Convergent validity was assessed by analysing the correlation between the WRVAS-TR and the Scoliosis Research Society-22 (SRS-22) scales. Results: The mean age of the patients was 12.8 years, maximum Cobb angle was 32.1° and maximum angle of trunk rotation was 9.9°. The intraclass correlation coefficient for the item-total score was 0.906 (p<0.001). The Cronbach’s alpha coefficient for all the seven items was 0.783. Self-image scores of the SRS-22 had significantly negative correlations with the 1st (p=0.03) and 4th (p=0.003) questions and the total WRVAS-TR scores (p=0.01). Conclusion: Improving the aesthetic appearance has been identified as one of the main goals of scoliosis management. For adolescents especially, cosmetic appearance is more important than the angles measured on X-rays. WRVAS-TR test-re-test results showed high reliability and significantly negative correlations with self-image scores of the SRS-22.